Model of fuzzy risk assessment of the information system - ZHAO Dong-mei1; MA Jian-feng1; WANG Yue-sheng2 (Tongxin xuebao)
A model of risk assessment was introduced to the estimation of the information system.The method,which combined AHP and fuzzy logical method,was applied to the risk assessment.AHP and fuzzy logical method were altered according to the actual condition of the risk assessment of information system.Applying fuzzy logical method,the im-portant degree of each factor was judged in the aspects of the probability,the impact severity and uncontrollability,not judged immediately.Finally,the risk value of each factor was calculated.By comparing the risk value of each factor,it is known that which risk can take measures to control.By introducing entropy,the proportion of each risk factor in the whole risk assessment system was calculated.Next the risk degree of the whole system was calculated.Then the risk level of the whole system can be determined.The study of the case shows that the model can be easily used to the risk assessment of the information system security.The results are in accord with the reality.